THE NEED ANALYSIS FOR INTERACTIVE MULTIMEDIA BASED ON SCIENTIFIC LITERACY IN PRIMARY SCHOOL - Cucu Mardiana; Ghullam Hamdu; Seni Aprilia (Jurnal Cakrawala Pendas, 2025)
The low science literacy of students in Indonesia is a challenge in education, especially at the elementary school level. Science literacy plays an important role in developing critical thinking skills, problem solving, and understanding of scientific and technological phenomena. However, PISA results show that Indonesian students' science literacy scores are below the international average. Factors that contribute to this condition include the lack of interesting learning media, the use of conventional methods, and the lack of technology integration in science learning. Therefore, this study aims to analyze the need for interactive learning media to improve the science literacy of elementary school students. The research method used was descriptive qualitative with data collection techniques through interviews and documentation studies. Interviews were conducted with teachers and students in Cigugur Sub-district, Pangandaran Regency, to understand their experiences, constraints and expectations of interactive learning media. The results showed that students are more interested in digital-based interactive media, such as video animation, educational games, and interactive simulations. Teachers also recognize that the use of digital media can improve students' understanding and motivation to learn, although they face constraints such as lack of training and access to adequate digital devices. These findings indicate the need for development and training in the use of digital media that is easily accessible and applicable in the classroom, to support the continuous improvement of science literacy at the primary school level.